Mercury and Cyanide Contaminations in Gold Mine Environment and Possible Solution of Cleaning Up by Using Phytoextraction - NURIL HIDAYATI; TITI JUHAETI; FAUZIA SYARIF (Bogor Agricultural University, Indonesia, 2009)
Water contamination with heavy metals, mainly mercury and cyanide (CN) due to small scale of public mines and large scale of industrial mines have been in concern to residents around the area. Surveys of heavy metal contamination in aquatic environments, such as rivers and paddy fields over two gold mine areas in West Jawa were conducted and possible solution of using indigenous plants for phytoremediation was studied. The results showed that most of the rivers and other aquatic environments were affected by gold mine activities. Rivers, ponds, and paddy fields around illegal public mines were mostly contaminated by mercury in considerably high levels, such as paddy fields in two locations (Nunggul and Leuwijamang, Pongkor) were contaminated up to 22.68 and 7.73 ppm of Hg, respectively. Whereas rivers located around large scale industrial mines were contaminated by CN. Possible solution of cleaning up by using green technology of phytoremediation was examined. Some plant species grew in the contaminated sites showed high tolerance and potentially effective in accumulating cyanide or mercury in their roots and above ground portions. Lindernia crustacea (L.) F.M., Digitaria radicosa (Presl) Miq, Paspalum conjugatum, Cyperus kyllingia accumulated 89.13, 50.93, 1.78, and 0.77 ppm of Hg, respectively. Whereas, Paspalum conjugatum, Cyperus kyllingia accumulated 16.52 and 33. 16 ppm of CN respectively. Key words: phytoextraction, contaminants, cyanide, mercury